Response of Rice Somatic Embryogenesis to Exogenous Melatonin About Its Role in Scavenging Reactive Oxygen Species - Ubaidillah, Mohammad; Al Ayyubi, Nabila Nur Aisyah; Khofifa, Rendryana Aulia Nur; Dewanti, Parawita (AGRIVITA Journal of Agricultural Science, 2024)
The success rate of explant morphogenesis in plant breeding using tissue culture techniques is frequently plagued by browning due to the oxidation of phenolic compounds. The cumulated amount of reactive oxygen species (ROS) drives the oxidation of phenolic compounds. Melatonin is reported to take a part in modulating the regulation of antioxidant gene expression, reducing the accumulation of reactive oxygen species, and enhancing the efficacy of tissue culture. This study aims to determine the optimal melatonin concentration on the efficiency of plantlet regeneration and expression of the antioxidant resistance gene in rice callus. This study utilizes rice TN1, Gogo Niti II, Ketan Hitam, and Cigeulis cultivars. Melatonin at 0, 10, and 15 µM concentrations is supplemented in plantlet regeneration media. Rice antioxidant-related genes, Mn-SOD, Cu/ZnSOD, Cytosolic APX, CAT, GPOD, OsAPX, and OsCATA, expressed after melatonin supplementation. Melatonin concentration at 10 µM generates the highest expression of all tested genes in TN1 compared to other varieties. The cumulated amount of hydrogen peroxide (H2O2) shows that Melatonin has the potential to increase the proportion of plant regeneration in Cigeulis (90.48%) and Ketan Hitam (91.67%) varieties with a concentration of 10 µM and in TN1 (94.44%) and Gogo Niti II (80%) at a concentration of 15 µM.